iPhone for dummies - Baig, Edward C.; LeVitus, Bob (For Dummies, 2022)
My phone, your phone, iPhone--the fully updated guide to the latest models and iOS updates Apple seems to update its iPhone at the speed of light, and Dummies helps you keep up. iPhone For Dummies, 2022 Edition includes the newest features available with iOS 15, released in 2022. This version also covers all iPhone models available in 2022 including the iPhone 12, iPhone 11, iPhone XR, and iPhone SE. Whether you have a new iPhone or an older iPhone, you've got this book to walk you through everything your phone can do. The iPhone is a music player, a gaming system, a computer, and a mobile phone all wrapped up in one pocket-sized package. Your device can keep you connected, help you be productive, and provide endless hours of entertainment. iPhone For Dummies offers the insight of two longtime Apple experts on how to make the most of your iPhone and its updated features. Set up your device and learn about the apps and utilities that can help you get the most out of iPhone Understand important settings, privacy controls, and customizations to make your phone truly yours Snap photos, shoot videos, record audio and discover iPhone's many creativity tools Enter the wild world of apps using the app store, and find out about the latest hot downloads Ring! Ring! Pick up--it's your new iPhone calling.